A sensitive scale to assess nociceptive pain in patients with disorders of consciousness. Issue 12 (20th August 2012) - Chatelle, Camille; Majerus, Steve; Whyte, John; Laureys, Steven; Schnakers, Caroline
Abstract : Objective: To determine the sensitivity of the Nociception Coma Scale (NCS), the first scale developed to assess nociceptive pain in vegetative state and minimally conscious state patients, in comparing behavioural changes in response to noxious versus non-noxious stimulation. Methods: The NCS was administered to assess patients' responses in three conditions: (1) baseline (observation of spontaneous behaviours), (2) non-noxious/tactile stimulation (taps on the patient's shoulder), and (3) noxious stimulation (pressure on the nail bed). Results: We included 64 patients (27 vegetative state and 37 minimally conscious state; age range 20–82 years; 22 traumatic brain injury; 21 in the acute stage). The NCS total scores and subscores (motor, verbal and facial) were higher for the noxious versus the non-noxious stimulation conditions. We did not observe a difference between the non-noxious and the noxious stimulation conditions for the visual subscale. We also found a NCS cut-off value of 4 differentiating the patients receiving a noxious stimulation from patients receiving a non-noxious stimulation. The exclusion of the visual subscale increased the cut-off sensitivity (from 46% to 73%; specificity of 97% and accuracy of 85%). Conclusion: We propose a new version of the NCS excluding the visual subscale, the NCS-R, which constitutes a highly sensitive tool to assess responses to nociceptive pain in severely brain injured patients.